The making of the King James Bible - Griffith, Jerry; Rainolds, John, 1549-1607.; Allen, Ward, 1922-; Greenspoon, Leonard J. (Leonard Jay); Nicolson, Adam, 1957-; Christian History Magazine; Vision Video (Firm) (Cartesian Coordinates ; Worcester, Pa. : Vision Video [distributor], 2010)
The year 2011 marks the 400th anniversary of the creation of the King James Bible, arguably the greatest piece of English Literature ever produced. King James had an uncanny love of beautiful things, including language to stir the soul. With several English translations in use across the Kingdom, the Puritan leader John Rainolds took his opportunity to suggest that a new, more accurate translation was needed for the people. "Award-winning director Jerry Griffith... brings the viewer right into the heart of the translation process through specific passage examples. While exploring the varying viewpoints of different scholars, we get a firsthand look at the immense attention to detail. This presentation gives the viewer a renewed appreciation for the sacred scriptures and their place in our homes, churches, and the English-speaking world."
DVD; all regions.
English dialogue; English subtitles.
Title from container.
Director, Jerry Griffith.
Special features: extended interviews with Ward Allen, Leonard Greenspoon and Adam Nicolson.
Keywords: Bible. -- History; Bible -- Versions; Bible. -- History; Video recordings for hard of hearing people; Documentary films; Nonfiction films; Christian films